Biomolecules of the Horseshoe Crab’s Hemolymph: Components of an Ancient Defensive Mechanism and Its Impact on the Pharmaceutical and Biomedical Industry - Md. Ashrafuzzaman; Mamudul Hasan Razu; Nazmir-Nur Showva; Tohmina Afroze Bondhon; Md. Moniruzzaman; Sad Al Rezwan Rahman; Md. Raisul Islam Rabby; Fatema Akter; Mala Khan (Cellular Microbiology)
Without adaptive immunity, invertebrates have evolved innate immune systems that react to antigens on the surfaces of pathogens. These defense mechanisms are included in horseshoe crab hemocytes’ cellular responses to pathogens. Secretory granules, large (L) and small (S), are found on hemocytes. Once the invasion of pathogens is present, these granules release their contents through exocytosis. Recent data in biochemistry and immunology on the granular constituents of granule-specific proteins are stored in large and small granules which are involved in the cell-mediated immune response. L-granules contain most clotting proteins, which are necessary for hemolymph coagulation. They also include tachylectins; protease inhibitors, such as cystatin and serpins; and anti-lipopolysaccharide (LPS) factors, which bind to LPS and agglutinate bacteria. Big defensin, tachycitin, tachystatin, and tachyplesins are some of the essential cysteine-rich proteins in S-granules. These granules also contain tachycitin and tachystatins, which can agglutinate bacteria. These proteins in granules and hemolymph act synergistically to fight infections. These biomolecules are antimicrobial and antibacterial, enabling them to be drug resistant. This review is aimed at explaining the biomolecules identified in the horseshoe crab’s hemolymph and their application scopes in the pharmaceutical and biotechnology sectors.